2019
DOI: 10.1038/s41598-019-45545-w
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Mammalian CRES (Cystatin-Related Epididymal Spermatogenic) Amyloid is Antiparallel β-Sheet Rich and Forms a Metastable Oligomer During Assembly

Abstract: An amyloid matrix composed of several family 2 cystatins, including the reproductive cystatin CRES, is an integral structure in the mouse epididymal lumen and has proposed functions in sperm maturation and protection. Understanding how CRES amyloid assembles in vitro may provide clues on how the epididymal amyloid matrix forms in vivo . We therefore purified full-length CRES under nondenaturing conditions and followed its aggregation from monomer to amyloid under c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 71 publications
4
27
0
Order By: Relevance
“…The former has been shown to promote unilateral nucleation of IAPP, albeit with a lower efficiency compared to homologous assembly, whereby these proteins harbour stretches sharing sequence homology [172]. Several additional proteins have been associated to templated amyloid cross-talk via sharing of common structural architectures [161,[173][174][175], with the list expanding even to cases of functional amyloids [176][177][178][179][180][181][182]. Finally, cross-seeding and heterotypic co-aggregation has also been demonstrated in cancer-associated aggregation pathologies, where mutant p53 causes sequence-dependent co-deposition of its homologs p63 and p73 by virtue of their similar APRs [183][184][185].…”
Section: Is Sequence Specificity a Determining Factor In Amyloid Hetementioning
confidence: 99%
“…The former has been shown to promote unilateral nucleation of IAPP, albeit with a lower efficiency compared to homologous assembly, whereby these proteins harbour stretches sharing sequence homology [172]. Several additional proteins have been associated to templated amyloid cross-talk via sharing of common structural architectures [161,[173][174][175], with the list expanding even to cases of functional amyloids [176][177][178][179][180][181][182]. Finally, cross-seeding and heterotypic co-aggregation has also been demonstrated in cancer-associated aggregation pathologies, where mutant p53 causes sequence-dependent co-deposition of its homologs p63 and p73 by virtue of their similar APRs [183][184][185].…”
Section: Is Sequence Specificity a Determining Factor In Amyloid Hetementioning
confidence: 99%
“…1 C ). This observation, however, was not unexpected based on prior CD, FTIR, X-ray crystallization, and NMR studies of the related CRES that also revealed an antiparallel β-sheet-rich structure ( 25 , 26 ).
Figure 1 CRES3 forms SDS-sensitive and SDS-resistant aggregates.
…”
Section: Resultsmentioning
confidence: 75%
“…We next determined if the CRES3 seeds could template assembly of the related amyloidogenic precursor CRES. Because CRES is less aggregation-prone than CRES3 and other subgroup members, in previous studies we were able to isolate a tagless full-length mouse CRES C48A under nondenaturing conditions from the soluble fraction of bacteria and follow its assembly to amyloid ( 25 ). The free cysteine (C) at position 48 was mutated to alanine (A) to prevent improper disulfide bond formation during purification.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations